Life time of some RNA products of rDNA intergenic spacer in HeLa cells - Vacík, T; Kereïche, S; Raška, I; Cmarko, D; Smirnov, E (Histochemistry and cell biology, 2019)
In human cells, the intergenic spacers (IGS), which separate ribosomal genes, are complex approximately 30 kb-long loci. Recent studies indicate that all, or almost all, parts of IGS may be transcribed, and that at least some of them are involved in the regulation of the ribosomal DNA (rDNA) transcription, maintenance of the nucleolar architecture, and response of the cell nucleus to stress. However, since each cell contains hundreds not quite identical copies of IGS, the structure and functions of this locus remain poorly understood, and the dynamics of its products has not been specially studied. In this work, we used quantitative PCR to measure the expression levels of various rDNA regions at different times after inhibition of the transcription by Actinomycin D applied in high doses. This approach allowed us to measure real or extrapolated half-life times of some IGS loci. Our study reveals characteristic dynamic patterns suggestive of various pathways of RNA utilization and decay.
Keywords: mezerníky ribozomální DNA; HeLa Cells; DNA, Ribosomal Spacer; lidé; HeLa buňky; RNA; Humans